Beyond Reach: Social Media Performance as A Key Metricfor Marketing Success - Roosdhani, Mohamad Rifqy; Arifin, Samsul; Manaf, Khamisah Abd (Ilomata International Journal of Management, 2024)
Social media is now an integral part of business activities. Companies that manage social media effectively can experience significant benefits in improving their marketing performance. Study results show that there are still many businesses that have not developed effective social media strategies in their marketing efforts. This study explores the social media marketing strategies that Micro, Small, and Medium Enterprises (SMEs) should adopt to improve their social media performance, which in turn will improve overall marketing results. To achieve optimal social media performance, social media marketing strategies adopted by SMEs should involve Social Media based Customer Engagement. This study adopted a quantitative approach and collected data from 265 SMEs in the food and beverage sector in Semarang, Solo, Kudus, and Jepara regions using a purposive sampling method. Data collected through questionnaires were used to test the empirical model using Structural Equation Modelling (SEM-AMOS). The results showed that the implementation of effective social media marketing strategies by SMEs can increase Social Media-based Customer Engagement, which in turn will have a positive impact on their social media performance. Increased customer engagement through social media can also be strengthened by the Brand Exposure strategy applied in marketing through social media.